(untitled) (Lapai Journal of Economics, 2022)
This study examined the moderating effect of audit committee financial expertise on the relationship between audit quality and earnings management among quoted consumer goods companies in Nigeria. Earnings management as dependent variable was proxied by discretionary accruals while audit quality is explained using audit fees and auditor industry specialization.The study adopted Ex post facto research design. Population included all the 21 companies in the consumer goods sector. The study purposively, sampled 17 out of the entire population for the purpose of data collection. The study covered the period 2012 to 2021. Secondary data were extracted from the annual accounts of the companies for the period of the study. The study employed the use of multiple regression technique to analyse the data. The result of the study showed that both audit fees and auditor industry specialization have positive significant relationship with earnings management when moderated by audit committee financial expertise. The study concluded that both variables can be used as determinants of real earnings management when there is a financial expert on the audit committee. From the findings, it was recommended that efforts should be made with respect to legislations to strengthen auditors’ quality in Nigeria by ensuring that audit committee members have financial expertise since it is a viable corporate governance tool towards enhancing reported earnings quality.